1984
DOI: 10.1302/0301-620x.66b1.6693483
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of idiopathic scoliosis. Biplanar spinal asymmetry

Abstract: A clinical, cadaveric, biomechanical and radiological investigation of the pathogenesis of idiopathic scoliosis indicates that biplanar asymmetry is the essential lesion. Many normal children have coronal plane asymmetry (an inconsequential lateral curvature of the spine), and certainly all have vertebral body asymmetry in the transverse plane, but when median plane asymmetry (flattening or more usually reversal of the normal thoracic kyphosis at the apex of the scoliosis) is superimposed during growth, a prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
138
0
5

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(148 citation statements)
references
References 0 publications
4
138
0
5
Order By: Relevance
“…The initial altered profile used to trigger the deformation process was obtained by imposing on the reference configuration a geometrical eccentricity representing the corresponding initiating hypothesis. The tested eccentricities included 3 mm linear shifts in the frontal (PA) [39] or in the sagittal (Lat) [27] plane (equivalent to a Cobb angle of 2°), 2°rotational shift in the transverse plane (Rot) [6,16,21,24] and combinations Lat-PA and Lat-Rot [12,18]. The initial altered profile was generated only for the first step, by simulating imposed eccentricities in the global axis system at the eighth thoracic vertebra, which was assumed to be the apical vertebra of the (future) scoliotic curve.…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial altered profile used to trigger the deformation process was obtained by imposing on the reference configuration a geometrical eccentricity representing the corresponding initiating hypothesis. The tested eccentricities included 3 mm linear shifts in the frontal (PA) [39] or in the sagittal (Lat) [27] plane (equivalent to a Cobb angle of 2°), 2°rotational shift in the transverse plane (Rot) [6,16,21,24] and combinations Lat-PA and Lat-Rot [12,18]. The initial altered profile was generated only for the first step, by simulating imposed eccentricities in the global axis system at the eighth thoracic vertebra, which was assumed to be the apical vertebra of the (future) scoliotic curve.…”
Section: Simulationsmentioning
confidence: 99%
“…Similarly, Sommerville [27] suggested that the deformity consists of a structural lordosis consequent to a failure of growth of the posterior elements. Other theories state that the deformity results from a reduction of the thoracic kyphosis in a fixed structural lordotic area, which under the influence of transverse or coronal plane asymmetry, rotates to the side and gives rise to a lateral curvature [12,18]. White [39] observed the presence of a slight physiological thoracic curve, thus he associated the prime scoliotic lesion with the precarious coronal balance of the spine and consequent asymmetrical loading of vertebrae, which might rotate into the convexity of the curve.…”
mentioning
confidence: 99%
“…The sagittal profile often deteriorates when the Harrington technique is used. The consequences include a flat back, an angular increase of lumbar lordosis below the fusion level and low back pain [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Patients were allowed to choose between two study groups [1], scientific exercises approach to scoliosis (SEAS) group or [2] usual physiotherapy (PT) group. There were 35 patients in the SEAS group and 39 patients in the PT group all of whom were followed up at 6 and 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…The exact aetiology of adolescent idiopathic scoliosis (AIS) is unknown [1][2][3] but is deemed to be multi-factorial and includes genetic predisposition, imbalance between anterior and posterior spinal growth, abnormalities in connective tissue, skeletal muscle, muscle contractile mechanisms and neurology. While surgery is a well-recognised treatment of AIS, the role of conservative therapies including exercises, physiotherapy, intensive rehabilitation programmes and bracing has been the source of much debate [4].…”
Section: Introductionmentioning
confidence: 99%